Religiosity as a Coping Strategy for Generation Z in Dealing with Anxiety: a Phenomenological Study of Religious Psychology - Raudhatul Jannah; Lila Suci Alfika; Siti Zahwa Fadhilla; Jauharotul Ulum; Surawan Surawan (MADINAH, 2026)
Mental health is a critical issue for Generation Z, particularly college students who face academic pressures, social demands, and rapid advancements in digital technology. These conditions often trigger anxiety, which impacts psychological well-being. This study aims to understand Generation Z students’ experiences with anxiety and how religiosity is utilized as a coping strategy. This study employs a qualitative approach with a phenomenological design involving five students from the State Islamic University of Palangka Raya through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The results indicate that anxiety is experienced in three main forms: academic anxiety, social anxiety, and anxiety about the future. Students utilize religiosity through religious practices (prayer, salat, and reading the Qur’an) as well as spiritual approaches (belief, surrender, and meaning-making). The novelty of this study lies in revealing religiosity as an active, contextual, and experience-based coping process, rather than merely a measured variable. The findings indicate that religiosity serves as a means of emotional regulation, meaning-making, and a source of optimism in coping with anxiety. In practical terms, this study highlights the importance of integrating spiritual approaches into mental health support programs for college students. Theoretically, this study contributes to the field of the psychology of religion by shedding light on religious coping among Generation Z.